Heresy - Parris, S. J., 1974- (London HarperCollins Publishers Ltd., 2010)
Introducing the monk Giodarno Bruno, magician, scientist, and heretic in a new series of historical thrillers for fans of C.J. Sansom and 'The Name of the Rose'.
Keywords: Philosophers -- Christian heretics -- Inquisition